Design and synthesis of new heterocyclic compounds containing 5-[(1H-1,2,4-triazol-1-yl)methyl]-3H-1,2,4-triazole-3-thione structure as potent hEGFR inhibitors - TÜRE, ASLI (My University, 2023)
© 2023 Informa UK Limited, trading as Taylor & Francis Group.EGFR is one of the important mediators of the signaling cascade that determines key roles in various biological processes such as growth, differentiation, metabolism and apoptosis in the cell in response to external and internal stimuli. In recent years, it has been proven that although this enzyme activity is tightly regulated in normal cells, if the enzyme activity cannot be controlled, it can lead to malignancy. EGFR is also considered a prominent macromolecule in targeted cancer chemotherapy. For this purpose, a comprehensive modeling studies were conducted against EGFR protein and novel molecules containing 5-[(1H-1,2,4-triazol-1-yl)methyl]-3H-1,2,4-triazole-3-thione structure were suggested to be synthesized. Among the synthesized molecules, compounds 7c, 8c, 8f and 8g were determined to have significant IC50 values. Compound 8g was found to have the IC50 value closest to the very well-known EGFR inhibitor Gefitinib with its noncompetitive inhibition form. K i value of compound 8g was calculated as 0.00232 µM. Communicated by Ramaswamy H. Sarma.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Yapısal Biyoloji; Moleküler Biyoloji; Structural Biology; Molecular Biology; 1; 2; 4-triazole-3-thiones; 4-triazoles; docking; hEGFR; molecular modeling; thiosemicarbazides